PENGARUH FORTIFIKASI KANDUNGAN BAHAN ORGANIK DARI PUPUK ORGANIK BERBAHAN BAKU FESES SAPI POTONG DAN FESES AYAM NIAGA PEDAGING TERHADAP PRODUKSI SEGAR RUMPUT GAJAH(Pennisetum purpureum) - Prayogi Sunu (Universitas Medan Area, 2015)
The purpose of this study was to determine the effect of commercial broiler chicken feces as mixing beef cattle feces to raw material organic fertilizer from organic material aspects of the content and determine the effect of fertilizer results fortification against the total production of fresh grass. The material used is beef cattle feces as much as 930 kg, the commercial broiler chicken feces 270 kg, 2.4 liter EM4. This research method using a completely randomized design (CRD) with four treatments (R), namely: R0: 100% beef cattle feces (50 kg), R1: beef cattle feces 85% (42.5 kg) of commercial broiler chicken feces + 15% (7.5 kg), R2: beef cattle feces 70% (35 kg) + commercial broiler chicken feces 30% (15 kg), R3: beef cattle feces 55% (27.5 kg) + commercial broiler chicken feces 45 ( 22.5 kg) with six replications. The results showed that the average content of organic material of R0, R1, R2, and R3, respectively 43 071% 34 075%, 27.815%, and 36 098%. Analysis of variance results showed that the average organic material are not using a commercial broiler chicken manure (R0) is higher than using each treatment compost. Results of the analysis showed uniform administration of composting grass effect is not significant (P> 0.05) on the production of fresh forage grass, presumably because it is not yet decomposed compost perfectly and the nutrient content of compost so low that has not quite provide additional nutrients needed by plants.